Graph-analytic method of approximate calculation of the levels and contours of noise from aircraft - Запорожець, О.І.; Картишев, О.О.; Чайковська, О.А. (Proceedings of National Aviation University (archive), 2007)
The paper presents substantiation of methodologies for evaluation of aircraft noise levels and noise countures using their acoustical characteristics approved in the certificate of aircraft type. The graphic analytical method of noise levels and noise contures is analysed. The comparison of certified noise levels and noise levels calculated for EPNL criteria is done using INM software.